Induction of apoptosis by gluconasturtiin-isothiocyanate (GNST-ITC) in human hepatocarcinoma HepG2 cells and human breast adenocarcinoma MCF-7 cells - Arumugam, Asvinidevi; Ibrahim, Muhammad Din; Kntayya, Saie Brindha; Mohd Ain, Nooraini; Iori, Renato; Galletti, Stefania; Ioannides, Costas; Abdull Razis, Ahmad Faizal (MDPI, 2020)
Gluconasturtiin, a glucosinolate present in watercress, is hydrolysed by myrosinase to form gluconasturtiin-isothiocyanate (GNST-ITC), which has potential chemopreventive effects; however, the underlying mechanisms of action have not been explored, mainly in human cell lines. The purpose of the study is to evaluate the cytotoxicity of GNST-ITC and to further assess its potential to induce apoptosis. GNST-ITC inhibited cell proliferation in both human hepatocarcinoma (HepG2) and human breast adenocarcinoma (MCF-7) cells with IC50 values of 7.83 µM and 5.02 µM, respectively. Morphological changes as a result of GNST-ITC-induced apoptosis showed chromatin condensation, nuclear fragmentation, and membrane blebbing. Additionally, Annexin V assay showed proportion of cells in early and late apoptosis upon exposure to GNST-ITC in a time-dependent manner. To delineate the mechanism of apoptosis, cell cycle arrest and expression of caspases were studied. GNST-ITC induced a time-dependent G2/M phase arrest, with reduction of 82% and 93% in HepG2 and MCF-7 cell lines, respectively. The same treatment also led to the subsequent expression of caspase-3/7 and -9 in both cells demonstrating mitochondrial-associated cell death. Collectively, these results reveal that GNST-ITC can inhibit cell proliferation and can induce cell death in HepG2 and MCF-7 cancer cells via apoptosis, highlighting its potential development as an anticancer agent.